The Black Box Module for Low-Level Fluorescence Detection Targeting Optogenetic Studies - Maret, Elizabeth; Diagne, Mohamed (Journal of Student Research, 2013)
In optogenetics, genetic labeling by enhanced yellow fluorescent protein (EYFP) indicates transfected neurons expressing light-gated channel proteins, Channelrhodopsin-2 (ChR2) and Halorhodopsin (NpHR) for millisecond timescale optical manipulation of neurons. However, poor spatial understanding of transfection relative to probing is responsible for blind stimulation in complex mammalian systems and necessitates histological analysis of brain tissue. Repeatable optogenetic studies on well-trained and valuable subjects are therefore impossible. We report here the Black Box Module as a novel fluorescence detection system targeting EYFP emission and used in conjunction with a co-axial waveguide “optrode.” Results of the Black Box Module’s fluorescence detection performance in a bench-top environment simulating EYFP fluorescence with rhodamine 6g are presented. We show the Box’s filtration system to be sensitive to the EYFP-like fluorescence of rhodamine and its concentration dependent emissions behaviors. We anticipate these results to be the initial foundation in integrating the Box into optogenetic studies as a tool for locating areas of ChR2 and NpHR transfection.